Pelatihan pembelajaran aktif bagi Guru MI di Kabupaten Gowa - Nurhaedah Nurhaedah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Active learning in primary school is a learning to enable students to learn actively. The result of the initial observation shows the primary school teachers have not implemented the active learning in their teaching maximally. This training involves 30 teachers from several primary schools in Tombolo Pao district of Gowa regency. The activities in the Active Learning Training for Primary School Teachers show satisfactory results, as the implementation of the training provides a great advantage of compile, implement and manage active learning activities in the learning process.